2021
DOI: 10.3390/jpm11050353
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Values of Preoperative Characteristics for 30-Day Mortality in Traumatic Hip Fracture Patients

Abstract: Hip fracture patients have a high risk of mortality after surgery, with 30-day postoperative rates as high as 10%. This study aimed to explore the predictive ability of preoperative characteristics in traumatic hip fracture patients as they relate to 30-day postoperative mortality using readily available variables in clinical practice. All adult patients who underwent primary emergency hip fracture surgery in Sweden between 2008 and 2017 were included in the analysis. Associations between the possible predicto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 52 publications
(85 reference statements)
1
25
0
Order By: Relevance
“…Of the variables analyzed, metastatic carcinoma, ASA classification, sex, CCI ≤ 4, age, dementia, congestive heart failure, hypertension, surgery using pins/screws, and chronic kidney disease were the most important for predicting mortality 1 year postoperatively. In contrast, a previous study from our group investigating 30-day postoperative mortality found that the most important predictors were age, hypertension, dementia, sex, ASA classification, RCRI, CCI, congestive heart failure, non-displaced cervical hip fractures, and cerebrovascular disease [ 8 ]. There was a significant overlap, with age, sex, ASA classification, CCI, dementia, congestive heart failure and hypertension being important for predicting both 30-day and 1-year mortality [ 8 ].…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…Of the variables analyzed, metastatic carcinoma, ASA classification, sex, CCI ≤ 4, age, dementia, congestive heart failure, hypertension, surgery using pins/screws, and chronic kidney disease were the most important for predicting mortality 1 year postoperatively. In contrast, a previous study from our group investigating 30-day postoperative mortality found that the most important predictors were age, hypertension, dementia, sex, ASA classification, RCRI, CCI, congestive heart failure, non-displaced cervical hip fractures, and cerebrovascular disease [ 8 ]. There was a significant overlap, with age, sex, ASA classification, CCI, dementia, congestive heart failure and hypertension being important for predicting both 30-day and 1-year mortality [ 8 ].…”
Section: Discussionmentioning
confidence: 83%
“…In contrast, a previous study from our group investigating 30-day postoperative mortality found that the most important predictors were age, hypertension, dementia, sex, ASA classification, RCRI, CCI, congestive heart failure, non-displaced cervical hip fractures, and cerebrovascular disease [ 8 ]. There was a significant overlap, with age, sex, ASA classification, CCI, dementia, congestive heart failure and hypertension being important for predicting both 30-day and 1-year mortality [ 8 ]. The increased importance of metastatic carcinoma and chronic kidney disease for predicting 1-year mortality is understandable as they are both chronic conditions with systemic, long-term effects; however, the remaining differences require further discussion.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations